Follicle‐stimulating hormone promotes age‐related endometrial atrophy through cross‐talk with transforming growth factor beta signal transduction pathway. Issue 2 (13th November 2014) - Zhang, Dan; Li, Jingyi; Xu, Gufeng; Zhang, Runjv; Zhou, Chengliang; Qian, Yeqing; Liu, Yifeng; Chen, Luting; Zhu, Bo; Ye, Xiaoqun; Qu, Fan; Liu, Xinmei; et al.
Summary It is widely believed that endometrial atrophy in postmenopausal women is due to an age‐related reduction in estrogen level. But the role of high circulating follicle‐stimulating hormone (FSH) in postmenopausal syndrome is not clear. Here, we explored the role of high circulating FSH in physiological endometrial atrophy. We found that FSH exacerbated post‐OVX endometrial atrophy in mice, and this effect was ameliorated by lowering FSH with Gonadotrophin‐releasing hormone agonist (GnRHa). In vitro, FSH inhibited endometrial proliferation and promoted the apoptosis of primary cultured endometrial cells in a dose‐dependent manner. In addition, upregulation of caspase3, caspase8, caspase9, autophagy‐related proteins (ATG3, ATG5, ATG7, ATG12 and LC3) and downregulation of c‐Jun were also observed in endometrial adenocytes. Furthermore, smad2 and smad3 showed a time‐dependent activation in endometrial cells which can be partly inhibited by blocking the transforming growth factor beta receptor II (TβRII). In conclusion, FSH regulated endometrial atrophy by affecting the proliferation, autophagy and apoptosis of endometrial cells partly through activation of the transforming growth factor beta (TGFβ) pathway.